Molecular mobility in polymers studied with thermally stimulated recovery. II. Study of the glass transition of a semicrystalline PET and comparison with DSC and DMA results - Alves, N. M. (2002)
The glass transition of a semicrystaline PET is studied by dinamic mechanical analysis (DMA) and thermally stimulated recovery (TSR). The DMA results allowed us to construct a master curve for E’ and D’, where the shift factors were modelled with the Vogel-Fulcher-Tamman-Hesse (VFTH) equation above Tg. Using the thermal sampling procedure the TSR technique allowed us to decompose the complex distribution of retardation times into a set of quasi-elementary processes. At the compensation point a broad distribution of retardation times is observed using DSC data. The TSR results show a typical increase of the activation energies in the glassy state, followed by a decrease above Tg that may be modelled with the VFTH equation. This observation was explained taking into account both the typical time scale range of TS experiments and the evolution of the retardation times distribution with temperatures below and above Tg, under the Adams-Gibbs theory. The evolution of the activation energies from TSR results was shown to be compatible with the DMA and DSC data.